Adhesion and interfacial characterization of biomimetically texturized lithium disilicate - Zorzin, José Ignacio; Beck, Simon; Belli, Renan; Petschelt, Anselm; Boccaccini, Aldo R.; Lohbauer, Ulrich (International Journal of Adhesion and Adhesives, 2019)
Lithium disilicate glass-ceramic (LS2) can be biomimetically textured by crystal orientation, mimicking the microstructure of dental enamel and inducing anisotropic mechanical responses to crack growth. The deliberate texturization of LS2 plays to the clinical advantage of reinforcing weak sites of typical fracture initiation in dental prosthetic constructs. Similar to enamel, adhesion of biomimetically textured LS2 could also show anisotropic behavior. Therefore, tensile bond strength (TBS) before and after thermocycling (TC) and interfacial characterization of biomimetically textured LS2 (parallel (PAR) or perpendicular (PER) crystal orientation) after different pre-treatment modes (hydrofluoric acid etching (HFE), grit blasting (GBL) and self-etching glass-ceramic primer (SGP)) were investigated. TC reduced significantly TBS for all specimens except for GBL. Biomimetic textured LS2 after HFE showed anisotropic behavior regarding adhesion. Crystal orientation reduced TBS for the PER HFE specimens after TC significantly. In general, the TBS of HFE specimens was still higher or not significantly lower compared to other pre-treatment modes like GBL or SGP. For the GBL and SGP specimens, crystal orientation had no influence on TBS and interfacial characteristics. In contrast HFE specimens showed different interfacial characteristics depending if they were PAR or PER texturized. Based on these findings, HFE of biomimetic textured LS2 can be recommended. For bonding, the PAR orientation is recommended as its adhesion potential is less prone to degrade.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Anisotropic; Biomimetic material; Grit blasting; Hydrofluoric acid etching; Interfacial characterization; Lithium disilicate ceramics; Self-etching glass-ceramic primer; Tensile bond strength

A re-usable 3D-printed training model for the endodontic management of dental trauma in immature teeth - Maier, Eva; Zentgraf, Jan; Angele, Eveline; Zorzin, José Ignacio; Taschner, Michael; Widbiller, Matthias; Galler, Kerstin Martina; Schratzenstaller, Thomas (International Endodontic Journal, 2025)
Aim: To develop a 3D-printed model enabling treatment simulation of trauma-related endodontic and restorative procedures like revitalization or placement of an apical plug on teeth with incomplete root formation. Methodology: To generate a realistic training model suitable for trauma-related simulations, CT-Data sets were segmented, combined, adjusted and optimized using computer-aided design features. Specific focus was on optimally reflecting characteristics of immature teeth like open apical foramina and thin root walls. For reflection of the revitalization process, a set-up including a tube filled with red liquid under pressure was developed to be perforated during the procedure by the trainee, simulating bleeding from the apical papilla into the root canal system. Design was based on a combination of cost-effective simple parts combined with 3D-printed components to achieve maximal accessibility, exchangeability and re-usability. Model assembly and preparation were described in step-by-step instructions. Results: As a result of the developmental process, the presented model qualifies for the training of the endodontic management of complications on immature teeth after dental trauma. Step-by-step descriptions aligned with the clinical procedures are performable for a revitalization procedure, for pulpotomy followed by fragment re-attachment and splint application and for placement of an apical plug using hydraulic calcium silicate cements. Conclusions: The model successfully achieved its intended objectives, so that it may be used in the future in various dental trauma treatment simulations for undergraduate and postgraduate education on the endodontic management of trauma-related therapies in immature teeth. Its common manufacturing process, affordability and re-usability support accessibility and sustainability.
CRIS-Team Scopus Importer:2025-04-18
Keywords: 3D-printing; dental education; dental traumatology; immature teeth; revitalization; training model

A split-Chevron-Notched-Beam sandwich specimen for fracture toughness testing of bonded interfaces - Lubauer, Julia; Belli, Renan; Lorey, Tony; Max, Stefanie; Lohbauer, Ulrich; Zorzin, José Ignacio (Journal of the Mechanical Behavior of Biomedical Materials, 2022)
The realization that the use of strength tests as a means to probe the bonding performance of adhesive systems to dental restorative materials suffers from inherent drawbacks has shifted efforts towards devising viable and valid fracture toughness test for that purpose. Here we introduce a new procedure to produce split-Chevron-Notched-Beam specimens that need not undergo sawing or notching after bonding, thus sparing the interface from pre-stresses. We evaluate the formal geometric factor considering the influence of the use of different materials having different elastic properties, and show that the results obtained fall within reasonable ranges measured by other established compliance calibrated methods. We demonstrate the application of this new approach for dentin-luting composite and zirconia-luting composite interfaces for different adhesive systems and pre-treatment procedures in order to probe the sensitivity of the method to different bond qualities.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Adhesion; Bonding; Chevron-notched-beam; Dentin; Fracture toughness; Zirconia

Bulk-fill resin composites: Polymerization properties and extended light curing - Zorzin, José Ignacio; Maier, Eva; Harre, Sarah; Fey, Tobias; Belli, Renan; Lohbauer, Ulrich; Petschelt, Anselm; Taschner, Michael (Dental Materials, 2015)
Signcance. All investigated bulk-fill composites obtained sufficient polymerization properties at 4 mm depth. Enhanced curing time improved the investigated polymerization properties of bulk-fills and Z250. (C) 2014 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Bulk-fill; Resin composites; Shrinkage stress; Volume shrinkage; Degree of conversion; Irradiance; Vickers hardness; FTIR spectroscopy

Crack growth behavior of a biomedical polymer-ceramic interpenetrating scaffolds composite in the subcritical regimen - Belli, Renan; Zorzin, José Ignacio; Petschelt, Anselm; Lohbauer, Ulrich; Tommaso Rocca, Giovanni (Engineering Fracture Mechanics, 2020)
We subjected a commercial dental composite formed by interconnecting polymer-ceramic scaffolds to extensive quasi-static, static and cyclic experiments under biaxial flexure. By this we meant to obtain static and cyclic subcritical crack growth exponents that, based on established relationships describing the degradation of frictional bridging mechanisms, challenging the notion of a suggested R-curve behavior. By exploring the fracture statistics of specimens with increasing effective volumes and effective areas, we demonstrated the presence of a bi-modal defect size distribution in disaccord with the Weibull behavior across length scales. Lifetime distributions seemed to follow the strength distributions, and were used to derive crack growth velocity diagrams for combined levels of applied stress. Ultimately, the claim of an R-curve behavior could not be supported based on the absence of any significant cyclic fatigue effect, i.e. bridging degradation.
CRIS-Team Scopus Importer:2020-04-03

Descriptions of crack growth behaviors in glass-ZrO2 bilayers under thermal residual stresses - Belli, Renan; Wendler, Michael; Zorzin, José Ignacio; Petschelt, Anselm; Tanaka, Carina B.; Meira, Josete; Lohbauer, Ulrich (Dental Materials, 2016)
This study was intended to separate residual stresses arising from the mismatch in coefficients of thermal expansion between glass and zirconia (ZrO2) from those stresses arising solely from the cooling process. Slow crack growth experimentes were undertaken to demonstrate how cracks grow in different residual stress fields.Aluminosilicate glass discs were sintered onto ZrO2 to form glass-ZrO2 bilayers. Glass discs were allowed to bond to the ZrO2 substrate during sintering or prevented from bonding by means of coating the ZrO2 with a thin boron nitrade coating. Residual stress gradients on "bonded" and "unbonded" bilayers were assessed using birefringence measurements. Unbonded glass discs were further tested under biaxial flexure in dynamic fatigue conditions in order to evaluate the effect of residual stress on the slow crack growth behavior.When fast-ccoling was induced, residual tensile stresses on the glass increased significantly on the side toward the ZrO2 substrate. By allowing the bond between glass and ZrO2, those tensile stresses observed in unbonded specimens are overwhelmed by the contraction mismatch stresses between the ZrO2 substrate and the glassy overlayer. Specimens containing residual tensile stresses on the bending surface showed a time-dependent strength increase in relation to stress-free annealed samples in the dynamic biaxial bending test, with this effect being dependent on the magnitude of the residual tensile stress. The phenomenon observed is explained here on the basis of the water toughening effect, in which water diffuses into the glass promoting local swelling. An additional residual tensile stress at the crack tip adds an applied-stress-independent (Kres) term to the total tip stress intensity factor (Ktip), increasing the stress-enhanced diffusion and the shielding of the crack tip through swelling of the crack faces.Residual stresses in the glass influence the crack growth behavior of veneered-ZrO2 bilayered dental prostheses. The role of water in crack growth might be of higher complexity when residual stresses are present in the glass layer.
EVALuna2:24680

Effect of Luting Materials on the Accuracy of Fit of Zirconia Copings: A Non-Destructive Digital Analysis Method - Berger, Lara; Matta, Ragai; Weiß, Christian; Adler, Werner; Wichmann, Manfred; Zorzin, José Ignacio (Materials, 2024)
The marginal accuracy of fit between prosthetic restorations and abutment teeth represents an essential aspect with regard to long-term clinical success. Since the final gap is also influenced by the luting techniques and materials applied, this study analyzed the accuracy of the fit of single-tooth zirconia copings before and after cementation using different luting materials. Forty plaster dies with a corresponding zirconia coping were manufactured based on a single tooth chamfer preparation. The copings were luted on the plaster dies (n = 10 per luting material) with a zinc phosphate (A), glass–ionomer (B), self-adhesive resin (C), or resin-modified glass–ionomer cement (D). The accuracy of fit for each coping was assessed using a non-destructive digital method. Intragroup statistical analysis was conducted using Wilcoxon signed rank tests and intergroup analysis by Kruskal–Wallis and Mann–Whitney U tests (α = 0.05). Accuracy of fit was significantly different before/after cementation within A (0.033/0.110 µm) and B (0.035/0.118 µm; p = 0.002). A had a significantly increased marginal gap compared to C and D, and B compared to C and D (p ≤ 0.001). Significantly increased vertical discrepancies between A and B versus C and D (p < 0.001) were assessed. Of the materials under investigation, the zinc phosphate cement led to increased vertical marginal discrepancies, whereas the self-adhesive resin cement did not influence the restoration fit.
CRIS-Team Scopus Importer:2024-05-24
Keywords: CAD–CAM technology; ceramics; dental materials; glass–ionomer cement; marginal fit; prosthodontics; resin-modified glass–ionomer cement; self-adhesive resin cement; zinc phosphate cement; zirconia

Effect of microparticulate silver addition in dental adhesives on secondary caries in vitro - Kraemer, Norbert; Moehwald, Mandy; Luecker, Susanne; Domann, Eugen; Zorzin, José Ignacio; Rosentritt, Martin; Frankenberger, Roland (Clinical Oral Investigations, 2015)
The aim of the present study was evaluate the effect of microparticulate silver additions in adhesives on secondary caries formation using an artificial mouth model.One hundred eight intact human third molars received standardized Class-V resin composite restorations (Filtek Supreme XTE bonded with Syntac, Scotchbond 1 XT, Futurabond M). Adhesives were charged with different amounts of microparticulate silver (0 %/0.1 %/0.5 %). After storage for 4 weeks at 37 °C, teeth were subjected to 10,000 thermocycles (+5 °C and +55 °C), and impressions were taken. Streptococcus mutans 10449 was used in a nutrition medium for secondary caries simulation in a fully automated artificial mouth. After completion of thermocycling and biological load cycling, impressions were taken and replicas were investigated under a light microscope for gap widths at enamel and dentin margins. Evaluation of fluorescence was carried out using a special FITC filter. The demineralization depths at the cavity margin were evaluated using Xpert for Windows working at a pixel distance of 5 ?m.After thermocycling, no difference in gap widths and demineralization depths was found (p > 0.05). After incubation, gap widths and demineralization depths were significantly reduced with higher amounts of silver loading in most of the adhesives (p < 0.05). The 0.5 % silver addition resulted in a slight decrease of secondary caries at resin-dentin margins (p < 0.05).Addition of microparticulate silver in commercially available dental adhesives has the potential of reducing secondary caries.The chosen setup was able to produce secondary caries with a distinct in vivo appearance. Microparticulate silver additions in dental adhesives may have an impact on inhibition of secondary caries.
EVALuna2:24674

Fracture toughness mode mixity at the connectors of monolithic 3Y-TZP and LS2 dental bridge constructs - Belli, Renan; Wendler, Michael; Zorzin, José Ignacio; da Silva, Lucas Hian; Petschelt, Anselm; Lohbauer, Ulrich (Journal of the European Ceramic Society, 2015)
Most dental ceramics are produced from partially crystallized glass. Even though these materials are hard, they are extremely susceptible to damage, especially due to the glass phase content. A strategy for strengthening these materials makes use of their microstructure to form reinforcing sites within the structural design. Such approach has potential for application with lithium disilicate (LS2) glass-ceramics, which contain needle-form Li2Si2O5 crystals that deflect oncoming cracks. By press injection of the glass melt through specifically oriented injection channels, crystals are aligned in patterns that lead to high mechanical anisotropy. Here we apply this approach in the context of monolithic dental bridges simulated by beams under 3-point bending. Notches at different distances from the midspan play the role of connectors, and the mixed-mode fracture toughness is measured at varying positions for a LS2 and a 3Y-TZP material. A strong anisotropic fracture behavior is obtained with the LS2 glass-ceramic through local crystal alignment, leading to fracture energies higher than for the isotropic 3Y-TZP ceramic. Further, the anisotropic nature of the LS2 microstructure is successfully reproduced in dental bridge geometries, validating the use of bending beams for the study of the mechanical behavior of ceramic dental bridges.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dental bridges; Fracture toughness; Lithium disilicate; Mixed-mode loading; Zirconia

Fracture Toughness Testing of Dental Restoratives: a Critical Evaluation - Belli, Renan; Zorzin, José Ignacio; Lohbauer, Ulrich (Current Oral Health Reports, 2018)
Purpose of Review: We intend by this short critical review to highlight important aspects regarding the mechanical testing of fracture toughness. The final aim is to increase the awareness to the test sensitivity, ultimately increasing the quality and reliability of reported testing results. Recent Findings: In a well-intended attempt to facilitate testing procedures or provide alternatives for testing material interfaces, authors are resorting to adaptation of testing methodologies without proper theoretical and experimental validation. The assumption of validity in such cases endangers the perpetration of testing strategies that are not safeguarded by sound theoretical bases. The use of improper statistical treatments based on extreme-value distributions further aggravates this scenario. Summary: We supply here some directions for authors concerning method selection, interpretation of data scatter, statistical treatment, and possibilities for test validation.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dental restorative materials; Fracture toughness; Mechanical properties; Testing

Hygroscopic expansion of self-adhesive resin cements and the integrity of all-ceramic crowns - Kirsten, Magdalena; Matta, Ragai Edward; Belli, Renan; Lohbauer, Ulrich; Wichmann, Manfred; Petschelt, Anselm; Zorzin, José Ignacio (Dental Materials, 2018)
OBJECTIVE: Low pH neutralization and subsequent remnant hydrophilicity can lead to hygroscopic expansion of self-adhesive resin cements (SARCs) after water storage. The aim of this in vitro study was to investigate the effects of hygroscopic expansion of SARCs, used as luting and partial core build-up material, on integrity and cement gap thickness increase of all-ceramic CAD/CAM crowns. METHODS: Human third molars (n=48) were prepared and anatomical all-ceramic CAD/CAM crowns were manufactured (VITABLOCS Mark II, VITA Zahnfabrik). Crowns internal surfaces were HF etched and silanized. The prepared teeth with their respective crowns were divided into 6 groups (n=8). In groups 1, 3 and 5 the coronal dentin was removed to simulate a partial core build-up. Groups 1 and 2 were luted with iCEM (Heraeus Kulzer), 3 and 4 with RelyX Unicem 2 Automix (3M), 5 and 6 with Variolink Esthetic DC (Ivoclar Vivadent). All specimens were dual cured and stored in distilled water at 37°C. Crown integrity was controlled at baseline and in regular intervals until 180 days. Cement gap thickness was measured using an optical 3D scanner (ATOS Triple scan, GOM) at baseline and after 180 days. Crown integrity was statistically analysed using Kaplan-Meier survival analysis and cement gap thickness increase using two-way ANOVA (α=0.05). RESULTS: After 180 days storage, crack formation was observed in all specimens of group 1 (mean survival time of 85.5 days), in one specimen of group 2 and in two specimens of group 4. Two-way ANOVA analysis revealed a statistically significant interaction between material type and build-up on cement gap size increase for iCEM. SIGNIFICANCE: Within the limits of this study, the application of SARCs with low pH neutralization as partial build-up material under CAD/CAM crowns is not recommended for clinical use.
EVALuna2:34637

Influence of Simulated Oral Conditions on Different Pretreatment Methods for the Repair of Glass-Ceramic Restorations - Höller, Benedikt; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich; Zorzin, José Ignacio (Journal of Adhesive Dentistry, 2022)
Purpose: The present study investigated the influence of simulated intraoral conditions (increased temperature and humidity) on two different surface pretreatment methods to repair a lithium-disilicate glass-ceramic (LDS).Materials and Methods: A total of 540 rectangular lithium-disilicate glass-ceramic bars were manufactured (3×7×9 mm; IPS e.max CAD, Ivoclar Vivadent). Further specimen preparation was performed in an incubator with controlled relative humidity (RH) and temperature to simulate three different environmental settings: laboratory conditions (LC, n = 180, 23°C, 50% RH), rubber-dam conditions (RC, n = 180, 30°C, 50% RH) or oral conditions (OC, n=180, 32°C, 95±5% RH). One-third of the bars under each condition (n=60) were grit blasted (GBL) with alumina (35 μm at 1 bar pressure for 10 s and a working distance of 4±1cm) and primed (60 s, Monobond Plus, Ivoclar Vivadent). Another third (n=60) were pretreated with a self-etching glass-ceramic primer (MEP, Monobond Etch & Prime, Ivoclar Vivadent). One group without surface pretreatment (n=60, NoPT) served as a control. All pre treated surfaces were coated with Heliobond (Ivoclar Vivadent). Two bars from the same pretreatment method were luted perpendicular to each other with a resin composite to form a square adhesion area of 9 mm2(TetricEvo Ceram, Ivoclar Vivadent), and light cured for 20 s on each side (1200 mW/cm2, Bluephase 20i, Ivoclar Vivadent). All specimens were stored for 24 h in distilled water at 37°C. Half of the specimens from each environmental set ting and pretreatment method (n=15) were thermocycled (TC, 5000 cycles, 5/55°C, 30-s dwell time), and tensile bond strength (TBS) testing was performed for all groups using an x-bar rope-assisted set-up. Data were statisti cally analyzed using two-way ANOVA (α=0.05) with Bonferroni adjustment.Results Regardless of the environmental and storage conditions (24 h or TC), MEP showed a significantly higher mean TBS than GBL. A decrease in TBS was recorded in specimens under OC compared to RC and LC for both pre treatment methods independent of the storage condition. No significant difference in mean TBS was found be tween RC and LC within the MEP pretreatment group for the 24 h stored and thermocycled specimens. For all MEPs and GBLs, TC reduced the mean TBS in all environmental conditions. The NoPT groups showed no adhesion regardless of environmental or storage conditions.Conclusions: Increased temperature and high humidity significantly reduced TBS. However, MEP was less sensitive to environmental influences than GBL, which makes it a promising candidate for intraoral ceramic repair. These findings suggest that clinical intraoral repair of lithium-disilicate glass-ceramics should be performed using a rub ber-dam, primarily when using GBL.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Grit blasting; Lithium-disilicate ceramic; Self-etching glass-ceramic primer; Silanization; Tensile bond strength; Thermocycling

New approaches in bonding to glass-ceramic: Self-etch glass-ceramic primer and universal adhesives - Maier, Eva; Bordihn, Vivien; Belli, Renan; Taschner, Michael; Petschelt, Anselm; Lohbauer, Ulrich; Zorzin, José Ignacio (Journal of Adhesive Dentistry, 2019)
Purpose: To investigate the tensile bond strength of silane-containing universal adhesives and self-etch glass-ceramic primer to lithium disilicate glass ceramics (LS2). Materials and Methods: 960 rectangular LS2 bars (7 mm x 3 mm x 9 mm, IPS e.max CAD, Ivoclar Vivadent) were manufactured and divided into 4 groups (n = 240). Group 1 was etched with 5% hydrofluoric acid (HF) for 20 s (VITA Ceramics Etch, Vita Zahnfabrik), group 2 was etched with 5% HF for 20 s and silanized (ESPE Sil, 3M Oral Care), group 3 was pre-treated with a self-etching glass-ceramic primer (Monobond Etch & Prime, Ivoclar Vivadent, and group 4 received no pre-treatment. Three universal adhesives (iBOND Universal, Heraeus Kulzer; Scotchbond Universal Adhesive, 3M Oral Care; Futurabond U, Voco) were applied to the differently pre-treated surfaces, with Heliobond (Ivoclar Vivadent) serving as control. The bars from each group were paired and luted perpendicularly, forming a square bonded area of 9 mm2, using Variolink II (Ivoclar Vivadent) with a constant pressure of 10 N, followed by light curing (40 s at 800 mW/cm2, Elipar Trilight, 3M Oral Care). The resulting specimens were stored for 24 h at 37°C in distilled water. Half of the specimens of each group were submitted to tensile bond strength testing, the other half were thermocycled ([TC] 5000 cycles, 5°C/55°C, 30-s dwell time) before testing. Data were analyzed using three-way ANOVA (α = 0.05). Results: Group 2 (HF etched and silanized) and group 3 (self-etching glass-ceramic primer) reached significantly higher mean bond strengths than did groups 1 (only HF etched) and 4 (no pre-treatment). Conclusion: Additional silanization of HF-etched LS2 statistically signficantly improved the tensile bond strength of the silane-containing universal adhesive (Scotchbond Universal). The self-etching glass-ceramic primer Monobond Etch & Prime achieved mean bond strengths that did not differ significantly from HF-etched and silanized specimens.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Lithium disilicate ceramic; Self-etch glass ceramic primer; Silanization; Tensile bond strength; Universal adhesive

PH neutralization and influence on mechanical strength in self-adhesive resin luting agents - Zorzin, José Ignacio; Petschelt, Anselm; Ebert, Johannes; Lohbauer, Ulrich (Dental Materials, 2012)
Objective: The aim of this study was to evaluate if pH-neutralization behavior of self-adhesive resin cements has an influence on their mechanical properties. Methods: pH-neutralization, water sorption, solubility and flexural strength of G-Cem Automix (GCA), G CEM Capsules (GCC), Maxcem Elite (MCE), RelyX Unicem Clicker (RXC), RelyX Unicem Maxicap (RXM), RelyX Unicem 2 (RX2), and Speed-Cem (SPC) were tested in self-curing mode. Specimen's pH-values were recorded up to 24 h with a pH-electrode. Water sorption (WS) and solubility (SO) were measured. Flexural strength (FS) was evaluated before and after thermocycling (TC) and fracture surfaces analyzed under SEM. Results: RX2 (pH 24 5.89), RXC (pH 24 5.49) and SPC (pH 24 5.42) showed highest 24 h pH-values, followed by GCA (pH 24 5.34). Capsulated products and MCE (pH 24 3.90) reached lower pH-values. GCC (75.78 μg/mm 3) showed the highest WS followed by MX (69.64 μg/mm 3), RXM (64.76 μg/mm 3), GCA (25.86 μg/mm 3) and SPC (30.42 μg/mm 3). Capsulated products RXM (56.58 μg/mm 3) and GCC (30.94 μg/mm 3) presented the highest SO, GCA (4.06 μg/mm 3) and SPC (4.26 μg/mm 3) revealed the lowest. GCA (114.03 MPa) had the highest initial FS followed by SPC (79.81 MPa), RXM (41.61 MPa) the lowest. FS of all materials decreased significantly after TC except for RXC (44.65 MPa) and RX2 (65.92 MPa). FS of GCC (16.47 MPa) and MCE (28.21 MPa) decayed the most. A highly linear correlation was observed between percentage decrease of FS after TC and 24 h pH-values (R 2 = 0.861). Significance: Within the limits of this study pH-neutralization behavior has an influence on mechanical stability. When using self-adhesive resin luting agents, automix-syringe products with improved pH-neutralization behavior should be favored. © 2012 Academy of Dental Materials.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dental cement; Flexural strength; Luting agent; Mechanical stability; pH; Physical behavior; Self-adhesive; Water solubility; Water sorption

Practical and theoretical considerations on the fracture toughness testing of dental restorative materials - Belli, Renan; Wendler, Michael; Zorzin, José Ignacio; Lohbauer, Ulrich (Dental Materials, 2018)
An important tool in materials research, development and characterization regarding mechanical performance is the testing of fracture toughness. A high level of accuracy in executing this sort of test is necessary, with strict requirements given in extensive testing standard documents. Proficiency in quality specimen fabrication and test requires practice and a solid theoretical background, oftentimes overlooked in the dental community.In this review we go through some fundamentals of the fracture mechanics concepts that are relevant to the understanding of fracture toughness testing, and draw attention to critical aspects of practical nature that must be fulfilled for validity and accuracy in results. We describe our experience with some testing methodologies for CAD/CAM materials and discuss advantages and shortcomings of different tests in terms of errors in testing the applicability of the concept of fracture toughness as a single-value material-specific property.
EVALuna2:24705

Removal of Radioactively Marked Calcium Hydroxide from the Root Canal: Influence of Volume of Irrigation and Activation - Zorzin, José Ignacio; Wiessner, Jessica; Wiessner, Thomas; Lohbauer, Ulrich; Petschelt, Anselm; Ebert, Johannes (Journal of Endodontics, 2016)
The purpose of this study was to evaluate the amount of calcium hydroxide (Ca[OH]2) removed by irrigation with different volumes and activation methods.One hundred thirty extracted straight, single-rooted human teeth were instrumented to size 45/.04. One hundred twenty teeth were filled with radioactively marked Ca(OH)2 and a gutta-percha point; 10 teeth with only gutta-percha served as a negative control. All specimens were stored in saline solution (7 days at 35°C). After storage, teeth were randomly divided into 12 groups (n = 10). The gutta-percha was taken out, and Ca(OH)2 was removed either by irrigation with different volumes (0 mL, 0.5 mL, 1 mL, 2 mL, 4 mL, or 8 mL) or mechanical activation with a 2- or 4-mL volume using a file (Instr) (FlexMaster size 45/.04; VDW, Munich, Germany), a brush (CanalBrush [CB]; Coltène/Whaledent, Langenau, Germany), or passive ultrasonic irrigation (PUI, smooth wire). Irrigation was performed by alternating 40% citric acid and 3% sodium hypochlorite. Residual Ca(OH)2 was measured by scintillation and expressed as a percentage of the original Ca(OH)2.Increasing the irrigation volume led to a significant decrease (P < .05) of residual Ca(OH)2 (0 mL [98.5%], 0.5 mL [21.7%], 1 mL [16.5%], 2 mL [12.9%], 4 mL [8.7%], 8 mL [5.0%], and negative control [0.0%]). Activation led to less residual Ca(OH)2 (2 mL Instr [12.0%], 2 mL CB [11.7%], 2 mL PUI [9.1%], 4 mL Instr [8.5%], 4 mL CB [7.4%], and 4 mL PUI [6.2%]), with significant differences according to the PUI (P < .05).No irrigation procedure was able to remove Ca(OH)2 completely. PUI was the most effective activation method. However, irrigation with an 8-mL volume was the most effective.
EVALuna2:24681

Self-adhesive resin cements: adhesive performance to indirect restorative ceramics - Zorzin, José Ignacio; Belli, Renan; Wagner, Anna; Petschelt, Anselm; Lohbauer, Ulrich (Journal of Adhesive Dentistry, 2014)
To evaluate the bonding performance of self-adhesive resin cements to zirconia and lithium disilicate in self- and dual-curing modes before and after thermocycling.Rectangular bars (3 mm high, 3 mm wide, 9 mm long) were manufactured from zirconia (Vita In-Ceram YZ for inLab, VITA) and lithium disilicate blocks (IPS e.max Press, Ivoclar Vivadent) (n=240 per material). Zirconia bars were sandblasted (35 ?m Al2O3, 1.5 bar pressure). Lithium disilicate bars were HF etched (20 s, IPS Ceramic Etching Gel, Ivoclar Vivadent) and silanized with ESPE Sil (3M ESPE). Forty bars of zirconia were luted in twos perpendicular to each other as were 40 bars of lithium disilicate using RelyX Unicem Automix 2 (3M ESPE), G-Cem LinkAce (GC Europe) or Maxcem Elite (Kerr) in self- or dual-curing mode. Half of the specimens from each material were submitted to tensile bond strength (TBS) testing after 24-h storage in distilled water at 37°C, and half underwent TBS testing after thermocycling (5000 cycles, 5°C/55°C, 30-s dwell time). Bond strength values for each bonding substrate were analyzed using one-way ANOVA (Student-Newman- Keuls, ?=0.05).On zirconia, dual-curing resulted in significantly (p<0.05) higher tensile bond strengths compared to self-curing, with the exception of RelyX Unicem 2 after thermocycling. Thermocycling significantly (p<0.05) reduced the tensile bond strength of Maxcem Elite to zirconia in both curing modes. The TBS of self-adhesive cements to lithium disilicate showed no significant (p>0.05) difference between the different curing modes and after thermocycling.For most of the investigated self-adhesive cements, bond strengths to zirconia were increased by dual curing; this was not true for lithium disilicate. For luting on zirconia with self-adhesive cements, dual curing is strongly recommended in clinical situations.
EVALuna2:24671

Self-adhesive resin cements: pH-neutralization, hydrophilicity, and hygroscopic expansion stress - Rödel, Lena; Bednarzig, Vera; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich; Zorzin, José Ignacio (Clinical Oral Investigations, 2016)
The objective of the study was to investigate the relationship between pH-neutralization, hydrophilicity, and free hygroscopic expansion stress of self-adhesive resin cements (SARCs) after storage in artificial saliva.The SARCs RelyX Unicem Automix 2 (RX2, 3 M ESPE), iCEM (iCEM, Heraeus) and Maxcem Elite (MCE, Kerr) were under investigation in this study. Cylinders (height × diameter, 6 × 4mm) were prepared from each material and stored in artificial saliva (7d at 37 °C). Cylinder height was measured at baseline and after 7 days. After storage, the compression modulus was measured to calculate the free hygroscopic expansion stress. For pH-neutralization and hydrophilicity assessment, disks (height × diameter, 1 × 1.5 mm) were prepared, covered with electrolyte, and monitored over 24 h at 37 °C. Hydrophilicity was assessed using the static sessile drop technique at baseline and at different time intervals up to 24 h. Data were analyzed using one-way ANOVA and post hoc Student-Newman-Keuls test (S-N-K, ? = 0.05).After 24 h, RX2 (pH24h 4.68) had a significantly higher (p < 0.05) pH-value than MCE (pH24h 4.2) and iCEM (pH24h 3.23). iCEM showed the significantly highest hydrophilicity (p < 0.05) after 24 h (?24h 85.02°), while MCE resulted lower (?24h 113.01°) in comparison with RX2 (?24h 108.11°). The resulting hygroscopic expansion stress of iCEM (29.15 MPa) was significantly higher (p < 0.05) compared to RX2 (14.5 MPa) and MCE (21.02 MPa).The material with lowest pH-neutralization capacity displayed higher hydrophilicity after 24 h and higher hygroscopic expansion stress after 7 days compared to those with high pH-neutralization.Remnant hydrophilicity due to low pH-neutralization of SARCs could lead to cement interface stress build-up and long-term failure of silicate ceramic restorations.
EVALuna2:24695